Расчетные показатели пластинчатых теплообменников и некоторые аспекты рационального использования природных ресурсов - Бабич, Н. И. (НТУ "ХПИ", 2015)
Наведено дані аналізу щодо завищення розміру теплообмінної поверхні відносно розрахункового значення. Показано, що збільшення поверхні призводить не тільки до збільшення експлуатаційних витрат, але й до підвищення інтенсивності вичерпування природних ресурсів.

Data analysis for overstating the size of the heat exchange surface relative to the calculated value. It is shown that increasing the surface not only leads to an increase in operating costs, but also to increase the intensity of depletion of natural resources.
Calculation of this indicator plate heat exchangers and some aspects of natural resource management
Keywords: пластинчатые теплообменные аппараты; материалы; энергия; коэффициент эффективности; теплопередача